Using Mobile Educational Apps to Foster Work and Play in Learning: A Systematic Review - Hussain, Azham; Mkpojiogu, Emmanuel O.C.; Babalola, Elizabeth Tolulope (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The paper examined the use of mobile educational applications to foster work and play in learning. Three research questions were asked to guide the study. Fifty (50) articles pertaining to the use of mobile educational applications in classrooms were downloaded. Out of all these papers, thirty-five (35) relevant articles were selected for review after which twenty-five (25) were carefully read and searched so as to capture the required information for the analysis. The outcome of the review indicated that there are lots of mobile educational apps that can be used by educators to foster work and play in classroom teaching and learning thereby making the teaching and learning become mobile and attractive. This means that teachers make use of apps, internet and computers to teach in classroom, which makes teaching and learning more interactive, collaborative and replaces the conventional chalkboards. The study applied systematic literature methodology in order to achieve the goal of the research. The research outcome showed that some educators have not yet embraced the use of mobile educational apps for teaching and learning in classrooms especially in third world countries. It was recommended that teachers, curriculum planners, policy makers, administrators and caregivers should be provided with knowledge on the new trend of mobile learning and its importance to the education sector.